THE INFLUENCE OF THE PJBL ON LOCAL WISDOM OF BALINESE CUSTOMARY TRADITIONS ON CREATIVE THINKING SKILLS AND GOTONG ROYONG CHARACTER IN PANCASILA EDUCATION SUBJECT FOR FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Ni Made Wisudarini Pratiwi; I Wayan Lasmawan; I Gede Margunayasa (SOSIOEDUKASI, 2026)
The purpose of this research is to determine the influence of the Project Based Learning (PjBL) Model Based on Local Wisdom of Balinese Traditional Traditions on the Ability to Think Creatively and Character of Mutual Cooperation in Pancasila Education Subjects in Grade V Elementary School Students. Quantitative research methods, types of pseudo-experimental research approaches, and Non-Equivalent Control Group Design experimental research designs. The research population consisted of 195 elementary school students. The research sample was taken with simple random sampling of the class intake obtained, namely SD Negeri 7 Sumerta as an experimental group, and SD Negeri 4 Sumerta as a control group, thus the total sample number in this study was 32 students from SD Negeri 7 Sumerta (experiment), and 32 students from SD Negeri 4 Sumerta (control), so that the total sample amounted to 64 students in class V. The data collection instruments were a questionnaire on the character of mutual cooperation and a test of creative thinking ability. The prerequisite test for data analysis consisted of a normality test, a variance homogeneity test, a covariance matrix homogeneity, a correlation test between variables, a linearlity test, and an outlier test. Hypothesis testing was carried out with MANOVA. The results showed that the F value was 17.543 with a significance level of 0.000 in Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root. The Sig. value < 0.05 which means that there is a significant difference between the experimental group and the control group simultaneously in the two dependent variables. The conclusion is that the PJBL model based on local wisdom of Balinese traditional traditions has a significant effect on students' creative thinking skills and mutual cooperation character. The suggestion for the next research is to be able to carry out experimental research by integrating local wisdom with learning models that are relevant to the demands of the times in other learning.